Pushing or Pulling Your “Poison”: Clinical Correlates of Alcohol Approach and Avoidance Bias Among Inpatients Undergoing Alcohol Withdrawal Treatment - Piercy, Hugh; Manning, Victoria; Staiger, Petra K. (Frontiers in Psychology, 2021)
Introduction: Alcohol approach bias, the tendency to automatically move towards alcohol cues, has been observed in people who drink heavily. However, surprisingly, some alcohol-dependent patients demonstrate an alcohol avoidance bias. This inconsistency could be explained by the clinical or demographic profile of the population studied, yet this has not been examined in approach bias modification (ABM) trials to date. We aimed to determine the proportion of patients with an approach or avoidance bias, whether they differ on demographic and drinking measures and to examine the clinical correlates of approach bias. Method: These research questions were addressed using baseline data from 268 alcohol-dependent patients undergoing inpatient withdrawal treatment who then went on to participate in a trial of ABM. Results: At trial entry (days 3 or 4 of inpatient withdrawal) 155 (57.8%) had an alcohol approach bias and 113 (42.2%) had an avoidance bias. These two groups did not differ on any demographic or relevant drinking measures. Approach bias was significantly associated (albeit a moderate effect) with total standard drinks consumed in the past 30 days (r=.277, p=.001), but no other indices of alcohol consumption or problem severity. Conclusion: Whilst the majority of alcohol-dependent patients showed an alcohol approach bias, those with an avoidance bias did not differ in demographic or clinical characteristics, and strength of approach bias related only to recent consumption. Further research is needed to develop more accurate and personally-tailored measures of approach bias, as these findings likely reflect the poor reliability of standard approach bias measures.